Reflections: Sociotechnical Systems Design and Organization Change - Pasmore, William; Winby, Stu; Mohrman, Susan Albers; Vanasse, Rick (Journal of change management, 2019)
This paper traces the evolution of sociotechnical systems design from its origins in the coal mines of Great Britain to the present day and beyond, into our digital future. Conceived as a means of enhancing productivity while simultaneously providing more meaningful work, sociotechnical thinking gained ground in machine-driven work settings and later took a leap forward to aid the effectiveness of knowledge work. After a period of stagnation as popular fads such as total quality, reengineering and lean six sigma took hold, sociotechnical thinking is poised to reemerge as capabilities associated with new technologies are rapidly outpacing the development of new organizational designs. A recent sociotechnical systems design lab brought together a diverse group of academics, thinkers and practitioners to discuss the future of organization design, producing tantalizing insights into the world that is about to take shape. Finally, implications for change management in sociotechnical transformation are discussed.